“THE DIRECTION OF THE WHOLE OF THE FORCES AVAILABLE”: THE DISPUTED SPHERES OF MILITARY AND CIVIL AUTHORITY IN THE EASTERN CAPE (1877– 1878), NATAL (1879) AND ZULULAND (1888) - Laband, John (Scientia Militaria - South African Journal of Military Studies, 2013)
In the late Victorian British Empire, the spheres of authority of the civil and military powers were not unequivocally defined, and could lead to wrangles that threatened the efficient conduct of military operations. Three such disputes occurred in southern Africa between 1878 and 1888. In 1878, during the 9th Cape Frontier War, the high commissioner replaced the Cape ministry with a more compliant one to assert control over both the imperial and colonial forces engaged. During the Anglo-Zulu War of 1879, the lieutenant-governor of Natal disputed the right of the general officer commanding to deploy African levies raised and stationed in Natal along the Zululand border. In 1888, during the uSuthu Rebellion in Zululand, the governor interfered with the general’s military arrangements because he believed these arrangements affected his civil powers. To head off future disputes of this nature, the British government ruled in 1879 that the commander in the field always had to exercise full control over active operations, and in 1888 finally clarified in which circumstances the general in command assumed operational authority over both the colonial and imperial troops stationed in a colony.